Pengaruh Kompetensi, Objektivitas, Dan Sensitivitas Etika Profesi Terhadap Kualitas Hasil Audit Pada Kantor Akuntan Publik Provinsi Bali - Ni Wayan Wintari; Rai Dwi Andayani W (Hita Akuntansi dan Keuangan, 2023)
The research objective is to analyze the effect of competence, objectivity, and sensitivity of professional ethics on the quality of audit results. Auditor quality is the expertise and knowledge of auditors in finding and reporting violations in the accounting system. A high quality audit is the auditor's demand so that the financial statements of interested parties are a big responsibility. The population in this study were all auditors of Public Accounting Firms (KAP) in the Bali region who were still active. Of the 15 KAPs registered at the Indonesian Institute of Certified Public Accountants (IAPI) in 2020. Sampling was carried out using the purposive sampling method and the number of samples was 110 respondents. Questionnaires were used for survey data collection as the method in this study. Multiple linear regression analysis technique was used in this study for data analysis. From the results of the hypothesis test, it was found that competence, objectivity, and sensitivity of professional ethics had a significant positive effect on the quality of audit results. Competence is simultaneously shown in the value of the coefficient of determination.Keywords: competence, objectivity , sensitivity, audit quality